In‐depth probe of researching interfacial charge transfer process for organic solar cells: A promising bisadduct fullerene derivatives acceptor. Issue 15 (25th March 2019) - Li, Ming‐Yang; Yin, Hang; Sui, Ming‐Yue; Wang, Fei; Liu, Yan‐Hui; Sun, Guang‐Yan
Abstract: The charge transfer (CT) mechanism at the donor/acceptor (D/A) interface plays an irreplaceable role in the photoelectric conversion of efficient bulk‐heterojunction (BHJ) organic solar cells (OSCs), which affects the resulting competition between charge separation and charge recombination. Extensive CT studies have preferred monoadduct fullerene derivatives (M60, M70 ) due to their unique spherical geometry with fewer factors to consider. However, the effect of carbon cage size, substituent group properties and the number of CT properties have not been much discussed. Here, sulfur‐containing bisadducts (B60, B70 ) were selected to explore whether they are also suitable for CT research like classical monoadducts. Using density functional theory and time‐dependent density functional theory, interface stacking configuration, key parameters relevant to CT states, charge separation, and recombination rates were determined to confirm the characteristics ofB60 andB70 as a good acceptor applied to interfacial research. This work points to the CT mechanism along the route of DA → D*A → D + A − through a theoretical analysis and also provides candidates for the theoretical interface photoelectric process in BHJ OSCs: bisadduct fullerene derivatives as good acceptor materials. Abstract : The in‐depth probe of charge transfer mechanism is an important breakthrough to improve power‐conversion efficiency at the donor/acceptor interface. Monoadduct fullerene derivatives have always been used for the investigation of interfacial charge transfer processes. This article explores whether bisadduct fullerene derivatives can also be promising candidates for replacing monoadducts on theoretical interface optoelectronic research.